THE RELATIONSHIP OF SELF-ESTEEM AND SELF-EFFICACY WITH CAREER MATURITY OF STUDENTS FACULTY OF ECONOMICS, JAKARTA STATE UNIVERSITY - Ramadhan, Muhammad Hardi; Purwana, Dedi; Rachmadania, Rizki Firdausi (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2021)
This study aims to determine whether there is a relationship between Self-esteem and Self-efficacy with career maturity of students from the Faculty of Economics, State University of Jakarta, class of 2016. The research method used is a questionnaire method with quantitative and correlational approaches. The population in this study were students of the 2016 economics faculty, totaling 523 students. The sample used in this study amounted to 227 students using the Simple Random Sampling technique. Y variable data (Career Maturity) is secondary data, while the variables X1 (Self-esteem) and X2 (Self-efficacy) are primary data using a Likert scale model with modifications. The data was then tested for validity and reliability, then analyzed using descriptive analysis techniques, classical assumption tests, and correlation tests. The data analysis technique used IBM SPSS version 26. The results showed: (1) There was a positive and significant relationship between Self-esteem and career maturity as indicated by the correlation coefficient tcount > ttable with a value of 0.189> 0.130 and a significance level of 0.004. (2) There is a positive but not significant relationship between Self-efficacy and career maturity as indicated by the correlation coefficient tcount > ttable with a value of 0.160 > 0.130 and a significance level of 0.016. (3) And there is a positive relationship between Self-esteem and Self-efficacy with career maturity with the results of the calculated correlation coefficient (r) of 0.189 and 0.160 respectively and the significance level of 0.004 and 0.016, respectively. by using the calculation of product moment correlation analysis.